2016
DOI: 10.1080/13602004.2016.1147152
|View full text |Cite
|
Sign up to set email alerts
|

Active Ageing: Social and Cultural Integration of Older Turkish Alevi Refugees in London

Abstract: Ageing of migrants in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…This type of research is also critical for understanding how older displaced people can be supported in terms of durable solutions, especially once the reasons for displacement have ended. Most research on durable solutions focuses on older refugees who have been resettled to third (usually developed) countries (see Bloom, 1989;Bolzman, 2014;Chenoweth and Burdick, 2001;Oglak and Hussein, 2016;Slewa-Younan et al, 2016;Tran, 1991). There is a dearth of research on repatriation and local integration for older refugees, the two durable solutions most commonly available to them.…”
Section: Past Their Prime? Negative Impacts Of Ageist Stereotypes On mentioning
confidence: 99%
“…This type of research is also critical for understanding how older displaced people can be supported in terms of durable solutions, especially once the reasons for displacement have ended. Most research on durable solutions focuses on older refugees who have been resettled to third (usually developed) countries (see Bloom, 1989;Bolzman, 2014;Chenoweth and Burdick, 2001;Oglak and Hussein, 2016;Slewa-Younan et al, 2016;Tran, 1991). There is a dearth of research on repatriation and local integration for older refugees, the two durable solutions most commonly available to them.…”
Section: Past Their Prime? Negative Impacts Of Ageist Stereotypes On mentioning
confidence: 99%
“…Care by, and involvement of, family emerged as an important issue in older migrants’ access to, and use of, healthcare. Studies found that older migrants’ conceptions of family care are rooted in traditions that emphasise the reciprocity of care between children and parents (Oglak and Hussein, 2016; Saltus and Pithara, 2015). It was also perceived as a duty and obligation (Liu et al , 2017) and a cultural “golden rule” that they wished to uphold (Thyli et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some older migrants from Indian–Welsh and Caribbean origin, now living in Wales, regarded professional providers of home care to be more knowledgeable and better suited to their new living circumstances than family members (Saltus and Pithara, 2015). However, despite a traditional discourse on family care (Oglak and Hussein, 2016; Saltus and Pithara, 2015), preferences for the type of care were also shaped by personal circumstances, language barriers (Oglak and Hussein, 2016; Thyli et al , 2014; Suurmond et al , 2016), lack of knowledge of services, poor health literacy (Suurmond et al , 2016), cultural incompatibility of beliefs and language with healthcare professionals (Oglak and Hussein, 2016; Thyli et al , 2014) and perceptions about the quality of formal care (Oglak and Hussein, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the literature on ageing in place focuses on native‐born populations (May & Muir, 2015). Beyond the considerable body of work on retirement migration (e.g., King, Warnes, & Williams, 2000; Oliver, 2012), there is limited, though increasing research, on how migrant populations navigate ageing in destination societies (Baldassar, Wilding, Boccagni, & Merla, 2017; Bolzman & Vagni, 2018; Buffel, 2017; Ciobanu, Fokkema, & Nedelcu, 2017; Oglak & Hussein, 2016; Oliver, Blythe, & Roe, 2018; Zontini, 2015). Meanwhile, the literature on migrant attachments and belonging in local places usually focuses on the experiences of recently arrived migrants (Trąbka, 2019).…”
Section: Introductionmentioning
confidence: 99%